A brief overview of the Security discipline in Information Systems courses in Brazil - Cristani, Matheus de Jesus; Alves, Waldenir Cardoso; Pereira, Gabriel Fernando Knupp; Lazarin, Nilson Mori (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2020: Companion Proceedings of the 16th Brazilian Symposium on Information SystemsDO - 10.5753/sbsi.2020.13114, 2020)
The Brazilian law about personal data protection comes into force in 2020. In order to comply with this law, it is essential that technology professionals know information security techniques and concepts. This article aims to present an overview of the emphasis on teaching Information Security in Information Systems Bachelor Degree courses in Brazil, as well as a regional comparison.